Pemutaran Film ‘Иди и смотри’ Oleh Kedutaan Besar Federasi Rusia Di Jakarta: Perjuangan Anti-Perang Dalam Perang Dunia II - Saragih, Hondor; Manurung, Hendra; Pannyiwi, Rahmat; Hutabarat, Erny; Rezasyah, Teuku; Sugiono, Muhadi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The film Иди и Cмотри directed by Elem Klimov starring Aleksei Kravchenko and Olga Mironova delivers the anti-war struggle campaign during World War II (WW II) in Belarus. This 142-minute film was released on July 9, 1985, in Belarus (БеларусьФильм) and the Soviets (МосФильм). The gross income obtained reached USS 21 million. The period of Nazi German occupation in Belarus began with the German invasion of the Soviet Union without a declaration of war on June 22, 1941, known as Operation Barbarossa ended in August 1944 with the launch of Operation Bagration by the Soviets. The western part of Byelorussia (1940) became part of the Reichskommissariat Ostland in 1941. The German government in 1943 allowed local collaborators to establish a client state as Belarusian Central Rada existed until the arrival of Soviet troops managed to liberate that region. The Reichskommissariat Ostland was a civil occupation regime established by Nazi Germany in 1941 in the Baltic states such as Estonia, Latvia, and Lithuania, northeastern Poland, and the western part of the Belarusian Soviet Socialist Republic during WW II. The German decision to form the Reichskommissariat aimed to 1) exterminate the Jewish population, 2) prepare Lebensraum for the German people, 3) expel the native population, and 4) assimilate the remainder. However, this policy did not only apply to the Reichskommissariat Ostland but was applied to other Soviet territories occupied by Germany. Utilizing Einsatzgruppen A and B assisted by local troops, found more than one million Jews were killed as a result of the formation of the Reichskommissariat Ostland. The results of the German troop's deployment were to invade them by the takeover of large Soviet territories and the deliberate killing of unarmed civilians (genocide). Berlin leaders’ decision indeed has created an unforgettable human tragedy.